2017
DOI: 10.5152/turkjorthod.2017.16024
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Orthognathic Correction of Class II Malocclusion on the Perception of Social Characteristics

Abstract: Objective: To evaluate the influence on the perception of social characteristics after orthognathic treatment for the correction of Class II malocclusion. Methods:A cross-sectional study was conducted with the participation of 240 observers who evaluated images of individuals before and after orthognathic surgery for the correction of malocclusion. Based on the images, two different questionnaires were applied containing 44 questions each for evaluating social competence, intellectual ability, psychological ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…In this study, the adolescents answered preferred to maintain an intentional conversation with CG and people with Class II malocclusion (Figure 5), probably because they find this malocclusion more attractive than the others. In the study by Pithon et al [24] they stated that individuals with Class II malocclusion are more sociable after undergoing orthognathic surgery. This work demonstrated that both to flirt and to maintain a lasting relationship the adolescents preferred those who presented Class II malocclusion, being the most attractive, when compared to the other malocclusions analysed (Figures 6 and 7).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the adolescents answered preferred to maintain an intentional conversation with CG and people with Class II malocclusion (Figure 5), probably because they find this malocclusion more attractive than the others. In the study by Pithon et al [24] they stated that individuals with Class II malocclusion are more sociable after undergoing orthognathic surgery. This work demonstrated that both to flirt and to maintain a lasting relationship the adolescents preferred those who presented Class II malocclusion, being the most attractive, when compared to the other malocclusions analysed (Figures 6 and 7).…”
Section: Discussionmentioning
confidence: 99%